The Impact of Corporate Financial Performance on Greenwashing Propensity: An Analysis of Fortune 100 Firms in Indonesia - Muhammad Alif Farras Azzuhdi; Majidah Majidah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims at analyzing the influence of corporate financial performance on the tendency to engage in greenwashing among companies listed in the Fortune 100 Indonesia. Greenwashing is corporate practices that misleadingly portray an environmentally friendly image without substantive actions. Such actions are usually reflected in the company's  financial performance, namely: Profit Margin (PM), Return on Assets (ROA), and Debt to Equity Ratio (DER).  The research employs logistic regression analysis using secondary data from financial reports and sustainability reports of 41 Fortune 100 Indonesia companies from 2020 to 2023. The results indicate that increases in Profit Margin and Return on Assets significantly influence the propensity of companies engaging in greenwashing, while inclining in Debt-to-Equity Ratio does not. These findings suggest that companies with improved financial performance are more likely to practice greenwashing to maintain a positive image without allocating sufficient resources tor sustainability efforts. This study contributes to academic literature by strengthening empirical evidence on the relationship between financial performance and greenwashing. Additionally, the findings can serve as a reference for investors, regulators, and the public in identifying greenwashing practices and promoting corporate transparency and accountability in sustainability reporting.